2019
DOI: 10.1177/1087054719865780
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of ADHD and Depression Based on Cognitive Performance

Abstract: Objective: The aim of this study was to assess whether self-report scales and neuropsychological tests used for adult patients with ADHD can help to distinguish between ADHD-specific and depressive symptoms. Method: In a cross-sectional design, differences in self-report questionnaires and neuropsychological tests among clinical subgroups and healthy controls (HC) were evaluated. Patients in clinical groups were diagnosed with major depressive disorder (MDD) or ADHD with or without depressive symptoms accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Mehren et al (2019) showed that reaction time variability, significantly more pronounced in ADHD patients, could decrease with exercise. Sustained attention deficits as compared to controls were also reported by Weyandt et al (2013), as represented by the CPT II Standard Error of reaction time (Cohen's d = 0.798), as well as by Grane et al (2014) on the TOVA test; by Holst and Thorell (2017) on a Navon like task (ANCOVA = 0.53); by Maruta et al (2017) when measuring visual tracking performance with the Attention Network Test and Spatial Span of the WMS-III, and by Paucke et al (2019), with reduced alertness and higher variations in reaction times measured by the TAP test. More recently, Lin and Gua (2020), who went further by detailing specific differences for early-onset and late-onset ADHD participants when compared to healthy controls, showed that only early-onset individuals showed significant impairment in the CANTAB probability of hit (sustained attention) in a second model of multiple analysis, while initially both early and late onset groups had showed impairment.…”
Section: Attention and Processing Speedmentioning
confidence: 95%
“…Mehren et al (2019) showed that reaction time variability, significantly more pronounced in ADHD patients, could decrease with exercise. Sustained attention deficits as compared to controls were also reported by Weyandt et al (2013), as represented by the CPT II Standard Error of reaction time (Cohen's d = 0.798), as well as by Grane et al (2014) on the TOVA test; by Holst and Thorell (2017) on a Navon like task (ANCOVA = 0.53); by Maruta et al (2017) when measuring visual tracking performance with the Attention Network Test and Spatial Span of the WMS-III, and by Paucke et al (2019), with reduced alertness and higher variations in reaction times measured by the TAP test. More recently, Lin and Gua (2020), who went further by detailing specific differences for early-onset and late-onset ADHD participants when compared to healthy controls, showed that only early-onset individuals showed significant impairment in the CANTAB probability of hit (sustained attention) in a second model of multiple analysis, while initially both early and late onset groups had showed impairment.…”
Section: Attention and Processing Speedmentioning
confidence: 95%
“…Comparing individuals with ADHD to the group of individuals showing indications of other psychiatric disorders (CCG), fewer differences were observed, i.e., the ADHD group reported higher scores on their current (ADHD-SR; CAARS) and retrospective (WURS-K) ADHD symptoms but lower scores on depression (BDI). Hence, also in differentiation to patients having other psychiatric disorders, ADHD symptomatology seems to have a key role and appears to have clinical value [38,40,42]. Considering the fact that the majority of individuals in the CCG showed indications of mood disorders (37 of 53), higher depression scores appear logical and may serve as useful information to differentiate ADHD from depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the WURS was found to be of only limited value to differentiate between ADHD and the other psychological disorders in a further study of the same group, which revealed a high rate of false positives (16%) in individuals who either were diagnosed with other psychological disorders or reported depressive symptoms [38,39]. In contrast, in a more recent study, Paucke and colleagues highlighted the utility of both the WURS and some subscales of the CAARS in the differentiation of ADHD and major depressive disorder [40]. Further, McCann and Roy-Byrne examined the utility of a number of ADHD self-report scales for the diagnostic screening of adults referred for an ADHD evaluation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comorbid depression therefore presents important clinical challenges [12,13] since its co-occurrence leads to greater illness burden and complexity than those individuals with aADHD or depression alone [11]. On the other hand, there is growing evidence from neuropsychological and electrophysiological studies that suggests no significant difference in cognitive performance [14] or in absolute power in specific frequency band measuring by electroencephalography (EEG) between depressed and non-depressed aADHD [15][16][17][18]. These results may question the usefulness and reliability of objective markers in differentiating between ADHD and depressive symptoms in adults.…”
Section: Introductionmentioning
confidence: 99%